Validation of Cod maturity ogive in NAFO 3M. Effect of the reproductive ccycle moment on ogive estimation. - Sampedro-Pastor, Paz; Garabana-Barro, Dolores; Saborido-Rey, Francisco (2018)
The Flemish Cap (FC) survey is the source of the Atlantic cod maturity data for SSB estimation. FC survey takes place when females are resting and discrimination between spawning active and inactive females is still possible testing the presence of postovulatory follicles, that remains several months after spawning. However, the best moment for discriminate active spawning females is during the spawning season. For 2012 and 2014, the maturity ogives calculated during the spawning season and when females are resting were compared. Assuming a seasonal growth for cod in 3M, the moment in which maturity is estimated, had no effect on the ogives estimation. Thus, it is recommended to continue employing in the 3M cod assessment the maturity ogives produced with the FC survey information.